Case report: Multisystemic smooth muscle dysfunction syndrome: a rare genetic cause of infantile interstitial lung disease - Li, Qianying; Cui, Lidan; Su, Jun; Shen, Yuelin (Frontiers in Pharmacology, 2025)
Multisystemic smooth muscle dysfunction syndrome (MSMDS) is an autosomal dominant disorder caused by mutations in the ACTA2 gene, resulting in variable clinical manifestation and multi-organ dysfunction. Interstitial lung disease (ILD) is a rare phenotype of this condition. We describe a rare infant case of an 8-month-old boy who presented with progressively worsening dyspnea, along with intermittent episodes of respiratory distress and cyanosis since birth. A chest CT scan revealed typical signs of ILD. Additionally, the patient exhibited congenital mydriasis, aortic coarctation, PDA, and pulmonary hypertension. Whole-exome sequencing identified a de novo variant c.536G > A (p.Arg179His) in the ACTA2 gene. These findings confirmed the diagnosis of MSMDS. Despite intensive hospital-based pulmonary care and optimized therapy, the child passed away due to sudden cardiac and respiratory arrest on the 12th day of hospitalization. This case underscores the importance of considering MSMDS in the differential diagnosis of infantile ILD.